Get a Keen Grasp of the Inherent Relations between the Vision of a Human Community with a Shared Future and the Three Global Initiatives - Jianchao, Liu (Napredak, 2024)
The focus of this research is on the Global Civilization Initiative, the Global Development Initiative and the Global Security Initiative of General Secretary Xi Jinping as China’s unique and strategic response to the global society challenges and the vision of future progress. Economic growth is the foundation of security and civilization, while further work will show the importance of the vision of Chinese communists who, in the era of deep changes and crises, see a solution in the fact that the progress of other countries leads to the establishment of the world of wellbeing and safety. The three initiatives are inherently connected and mutually strengthening, which points to the road of progress of human society from three different perspectives – growth, security and civilization. China will work hard on their implementation in order to help the international community to achieve the United Nations 2030 Agenda for Sustainable Development and inject strong impetus into global economic growth because it is the pathway towards world peace and cooperation.